Aggregation induced emission (AIE) active 4-amino-1, 8-naphthalimide-Tröger's base for the selective sensing of chemical explosives in competitive aqueous media. Issue 17 (3rd February 2020) - Delente, Jason M.; Umadevi, Deivasigamani; Shanmugaraju, Sankarasekaran; Kotova, Oxana; Watson, Graeme W.; Gunnlaugsson, Thorfinnur
Abstract : The 4-amino-1, 8-naphthalimide Tröger's base based AIE-active supramolecular scaffold was synthesized and employed as a highly selective and sensitive fluorescent sensor for nitroaromatic explosives sensing in competitive aqueous media. Abstract : The 4-amino-1, 8-naphthalimide-Tröger's base fluorophore, TBNap-TPy, adorned with phenyl-terpyridine moiety was synthesised and assessed for its aggregation-induced emission (AIE) behaviour. TBNap-TPy was further employed as a fluorescent sensor for the discriminative sensing of π-electron-deficient nitroaromatic; the TBNap-TPy displaying the largest fluorescence quenching with high selectivity for picric acid, a harmful environmental pollutant widely used in the dye industries.